Is the Use of a Drain for Thyroid Surgery Realistic? A Prospective Randomized Interventional Study. (30th May 2013) - Deveci, Ugur; Altintoprak, Fatih; Sertan Kapakli, Mahmut; Manukyan, Manuk Norayk; Cubuk, Rahmi; Yener, Nese; Kebudi, Abut
Abstract : Background . The use of a suction drain in thyroid surgery is common practice in order to avoid hematomas or seromas. The aim of this study was to determine the efficacy of routine drainage after thyroid surgery. Methods . In this prospective randomized trial, 400 patients who underwent either a total thyroidectomy or lobectomy for thyroid disorders were randomly allocated to either the nondrainage (group 1) or the drainage (group 2) group. The volume of fluid collection in the operative bed, postoperative pain, complications, and length of hospital stay were then recorded. Results . Both groups were homogeneous according to age, gender, thyroid volume, type of procedure performed, and histopathological diagnosis. After assessment by USG, no significant difference was found between the groups in the fluid collection of the thyroid bed (P = 0.117 ), but the length of hospital stay was significantly reduced in group 1 (P = 0.004 ). Conclusions . In our experience, the use of drain for thyroid surgery is not a routine procedure. However, it should be used in the presence of extensive dead space, particularly when there is retrosternal or intrathoracic extension, or when the patient is on anticoagulant treatment. This trial was registered with clinical Trials.gov NCT01771523 .